Phase equilibria of palm oil, palm kernel oil, and oleic acid plus supercritical carbon dioxide and modeling using Peng-Robinson EOS - Hong, Seung-Ah; Kim, Jae-Duck; Kim, Jaehoon; Kang, Jeong Won; Kang, Ik-Joong (ELSEVIER SCIENCE INC, 2010)
Vapor-liquid equilibria of the binary supercritical carbon dioxide (scCO(2)) + oleic acid, scCO(2) + palm oil, and scCO(2) + palm kernel oil were measured at a wide range of temperatures from 333.2 to 373.2 K and pressures from 8.5 to 35 MPa in a circulation-type phase equilibrium apparatus. The samples from liquid and vapor phases were analyzed using UV-vis spectrometer and a liquid hold-up equipment. The phase equilibrium data were correlated with Peng-Robinson Equation of State (PR-EOS) using Wong-Sandler mixing rule and optimum values of binary interaction parameters were determined. The relative deviation between experimental data and predicted data was in the range of 6.9-8.7%, suggesting that the PR-EOS with Wong-Sandler mixing rule is capable of predicting the vapor-liquid equilibria of oleic acid + scCO(2), palm oil + scCO(2), and palm kernel oil + scCO(2). (C) 2010 Published by Elsevier B.V, on behalf of The Korean Society of Industrial and Engineering Chemistry.
Keywords: RICE BRAN OIL; VAPOR-LIQUID-EQUILIBRIA; CUBIC EQUATIONS; BINARY-MIXTURES; LEMON FLAVORS; ETHYL-ESTERS; MIXING RULE; SOYBEAN OIL; FRYING OIL; FATTY OILS